STUDY OF TOXIC HEAVY METAL REMOVAL BY DIFFERENT CHITOSAN/HYACINTHS PLANT COMPOSITE - & et al., Rashid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Water pollution with toxic heavy metals represents a most important problem, as a result of releasing these metals to ecological ambient without treatment, leading to their persistence and non-biodegradation. A variety of traditional methods are utilized as an attempt to remove heavy metals from waste water, but still without making any actual progress. In present work Eichhorniacrassipes (water hyacinth) root and shoot powder ,and ash case with chitosan are used as a removal system for heavy metals (HM), including lead, copper and cadmium from waste water via biosorption process .It was carried out by using two different experimental conditions: (i) heavy metal concentration (1000 ppm), with different pH values, ranged between 3-8 with a constant (HM) (ii) using variable (HM) concentrations with a range (250, 500, 750 and 1000 ppm). The results proved a good absorption for the hyacinths plant to the heavy metal ions especially chitosan /hyacinth shoot . Moreover, it was seen that highest removal (98%) of Pb (II), while was removed (98.2%) of Cu (II) and removed )96.8%) of Cd (II) where removal within 24 hr. On the other hand, FTIR spectra of composite materials showed only the characteristic of raw materials bands, which provided a strong indication of composite formation.